CsPbBr3/Cs4PbBr6 perovskite@COF nanocomposites for visible-light-driven photocatalytic applications in water - Kour, Prachi; Mukherjee, Shatabdi Porel (Journal of Materials Chemistry A, 2021)
For the first time, we have synthesized all-inorganic CsPbBr3/Cs4PbBr6 perovskite@COF nanocomposites under atmospheric conditions and tuned the crystal structures of the perovskite as well. The nanocomposite is reasonably stable and maintains its crystalline properties even when dipped into water for 60 minutes. The perovskite@COF nanocomposite shows efficient visible-light-driven photocatalytic performance to degrade Methyl orange (10 mL; 20-100 ppm). The rate of photodegradation was about 0.245 min(-1) with high catalytic activity and recyclability for three to six cycles.